The Relationship of Pharmacological Intrathecal Labor Analgesia in Normal Delivery with the Stability of Vital Sign of Newborn - Purwarini, Justina (British Journal of Healthcare and Medical Research, 2022)
Intrathecal Labor Analgesia (ILA) is a pharmacological therapy technique to reduce delivery pain. The research objective was to determine the relationship between ILA pharmacological therapy in normal delivery and the stability of the vital signs of newborns at X Hospital from January 2018 to May 2020. This study was conducted from September 2020 to January 2021 on 143 normal birth mothers with ILA pharmacological therapy and 943 mothers giving birth normal without pharmacological therapy. The results showed that there was no significant relationship between the APGAR score in the first minute of newborns with ILA pharmacological therapy in normal delivery p value = 0.369, the APGAR score in the fifth minute of newborns with ILA pharmacological therapy in normal delivery p value = 1,000 and the baby's heart rate. newborn with ILA pharmacological therapy in normal delivery p value = 0.616. There is a significant relationship between body temperature of newborns with pharmacological therapy in normal delivery p value = 0.001 and respiratory rate of newborns with pharmacological therapy in normal delivery p value = 0.045. Efforts made include advising mothers to breastfeed on demand, aiming to prevent hypoglycemia, which is a complication that often occurs in hypothermic babies and can cause respiratory problems. Health workers in delivery rooms to be more aware of newborn monitoring.